2022
DOI: 10.1002/mbo3.1341
|View full text |Cite
|
Sign up to set email alerts
|

An in‐house 45‐plex array for the detection of antimicrobial resistance genes in Gram‐positive bacteria

Abstract: Identifying antimicrobial resistance (AMR) genes and determining their occurrence in Gram‐positive bacteria provide useful data to understand how resistance can be acquired and maintained in these bacteria. We describe an in‐house bead array targeting AMR genes of Gram‐positive bacteria and allowing their rapid detection all at once at a reduced cost. A total of 41 AMR probes were designed to target genes frequently associated with resistance to tetracycline, macrolides, lincosamides, streptogramins, pleuromut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…(2020) confirmed that flo R was found to be the predominant gene conferring resistance to florfenicol in different animal-derived bacteria. Among the aminoglycosides, both aad D and aac A- aph D genes were identified, which is in line with previously published studies ( Qu et al., 2019 ; Kowalewicz et al., 2023 ). The aac A- aph D gene code for a multifunctional enzyme confers resistance to multiple aminoglycosides such as amikacin, gentamicin, tobramycin, and kanamycin ( Schwarz et al., 2018 ), while aad D gene codes for adenyltransferase enzyme confer resistance to neomycin, kanamycin, tobramycin, and paromomycin ( Batool et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…(2020) confirmed that flo R was found to be the predominant gene conferring resistance to florfenicol in different animal-derived bacteria. Among the aminoglycosides, both aad D and aac A- aph D genes were identified, which is in line with previously published studies ( Qu et al., 2019 ; Kowalewicz et al., 2023 ). The aac A- aph D gene code for a multifunctional enzyme confers resistance to multiple aminoglycosides such as amikacin, gentamicin, tobramycin, and kanamycin ( Schwarz et al., 2018 ), while aad D gene codes for adenyltransferase enzyme confer resistance to neomycin, kanamycin, tobramycin, and paromomycin ( Batool et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, it is necessary to research the AMR problem from more perspectives. For this reason, Gram-positive bacteria belonging to the family Staphylococcaceae , which are considered part of the commensal microbiota of the skin and mucous membranes of animals and humans, are also used as an indicator of resistance [ 16 ]. Within this family, two groups are distinguished: coagulase-positive Staphylococcus (CoPS) [ 17 ] and coagulase-negative Staphylococcus (CoNS) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%